The Effects of Methylphenidate on Goal-directed Behavior in a Rat Model of ADHD - Natsheh, Joman Y.; Shiflett, Michael W. (Frontiers in Behavioral Neuroscience, 2015)
Although attentional and motor alterations in Attention Deficit Hyperactivity Disorder (ADHD) have been well characterized, less is known about how this disorder impacts goal-directed behavior. To investigate whether there is a misbalance between goal-directed and habitual behaviors in an animal model of ADHD, we tested adult [P75-P105] Spontaneously Hypertensive Rats (SHR) (ADHD rat model) and Wistar-Kyoto rats (WKY), the normotensive control strain, on an instrumental conditioning paradigm with two phases: a free-operant training phase in which rats separately acquired two distinct action-outcome contingencies, and a choice test conducted in extinction prior to which one of the food outcomes was devalued through specific satiety. To assess the effects of Methylphenidate, a commonly used ADHD medication, on goal-directed behavior, we injected rats with either Methylphenidate or saline prior to the choice test. Both rat strains acquired an instrumental response, with SHR responding at greater rates over the course of training. During the choice test WKY demonstrated goal-directed behavior, responding more frequently on the lever that delivered, during training, the still-valued outcome. In contrast, SHR showed no goal-directed behavior, responding equally on both levers. However, methylphenidate administration prior to the choice test restored goal-directed behavior in SHR, and disrupted this behavior in WKY rats. This study provides the first experimental evidence for selective impairment in goal-directed behavior in rat models of ADHD, and how methylphenidate acts differently on SHR and WKY animals to restore or impair this behavior, respectively.